Correlation of FSTL1 and its paralogs with body composition in adult survivors of childhood cancer - Lucie Štrublová; Filip Zlámal; Tomáš Pískovský; Jan Kučera; Jana Fialová Kučerová; Tomáš Kepák; Jaroslav Štěrba; Julie Bienertová-Vašků (Scientific Reports)
Abstract This retrospective, cross-sectional study investigated the relationship between body composition and circulating plasma levels of follistatin-like proteins (FSTLs; FSTL1, FSTL4, and FSTL5) in adult survivors of childhood cancer. This is the first study to investigate the association between plasma levels of FSTL4, FSTL5 and skeletal muscle mass. The cohort consisted of 61 CCS (26 females and 35 males) aged 18–36 years (mean age 24.6 ± 4.4 years) who were followed up at the Long-Term Follow-Up Clinic of St. Anne’s Hospital in Brno, Czech Republic. The mean age at diagnosis was 10.9 ± 4.9 years, and the mean time after treatment was 12.0 ± 5.1 years. Body composition was assessed using anthropometric indicators and bioelectrical impedance analysis (BIA; InBody 370). Plasma FSTL levels were quantified using commercially available ELISA kits. Correlations were examined by linear regression analysis. A significant negative correlation was found between the FSTL1 plasma level and body fat mass index (BFMI), and a significant positive correlation was observed between FSTL1 and skeletal muscle mass index (SMI). Our results suggest that FSTL1 may be a potential indicator of adiposity and skeletal muscle loss in CCS.